The lncRNA HCG4 regulates the RIG-I-mediated IFN production to suppress H1N1 swine influenza virus replication - Cheng, Jinghua; Tao, Jie; Li, Benqiang; Shi, Ying; Liu, Huili (Frontiers in Microbiology, 2024)
Influenza A virus (IAV) nonstructural protein 1(NS1) is a virulence factor that allows the virus to replicate efficiently by suppressing host innate immune responses.Previously, we demonstrated that the serine (S) at position 42 of NS1 in H1N1 swine influenza virus (SIV) is a critical residue in interferon (IFN) resistance, thus facilitating viral infections. Here, by lncRNA-seq, a total of 153 differentially expressed lncRNAs were identified, and the lncRNA HCG4 was selected due to its significantly higher expression after infection with the NS1 S42P mutant virus. Overexpression of HCG4 enhanced IFN-β production and suppressed SIV infection, highlighting the potential antiviral activity of HCG4 against SIV. Further investigation suggested that HCG4 served as a positive feedback mediator for RIG-I signaling. It alleviated the inhibitory effect on RIG-I K63-linked ubiquitination by NS1 protein, thereby resulting in an increase in RIG-I-mediated IFN production. Taken together, our findings demonstrate that HCG4 modulates the innate immune response to SIV infection through K63-linked RIG-I ubiquitination, providing insights into the role of lncRNAs in controlling viral infections.